Psychometric Properties of the Short Versions of the EBP Beliefs Scale, the EBP Implementation Scale, and the EBP Organizational Culture and Readiness Scale. Issue 4 (20th July 2021) - Melnyk, Bernadette Mazurek; Hsieh, Andreanna Pavan; Gallagher‐Ford, Lynn; Thomas, Bindu; Guo, Jinhong; Tan, Alai; Buck, Jacalyn
Abstract: Background: Evidence‐based practice (EBP) is a problem‐solving approach to clinical decision making that leads to a higher quality and safety of health care. Three valid and reliable scales that measure EBP attributes, including the EBP Beliefs Scale, the EBP Implementation Scale, and the Organizational Culture and Readiness Scale for System‐Wide Integration of EBP, are widely used but require approximately 5 min each to complete. Shorter valid and reliable versions of these scales could offer the benefit of less time for completion, thereby decreasing participant burden. Aim: The aim of this study was to determine the psychometric properties of the three shortened EBP scales, adapted from the longer versions. Methods: This study used a descriptive survey design with 498 nurses who completed the three original EBP scales along with a shortened version of each scale. Exploratory factor analysis was conducted with principal components extracted to examine the factor structure of each EBP measure for the three shortened EBP scales. Item intercorrelations and the Kaiser–Meyer–Olkin Measure of Sampling Adequacy (KMO) were used to confirm the validity of using factor analysis. Reliability of each scale using Cronbach's α was examined. Convergent validity of the three shortened EBP scales was assessed by correlating each shortened scale with its longer scale. Results: Factor analysis supported the construct validity of each of the three shortened scales, as all item intercorrelations were greater than 0.40, and KMO values were 0.62 to 0.74. The shortened scales Cronbach alphas were 0.81 for the EBP Beliefs Scale, 0.89 for the EBP Implementation Scale, and 0.87 for the EBP Culture and Readiness Scale. The three shortened EBP scales had acceptable convergent validity ( r  = 0.42–.072) for the correlations between the shortened and longer scales. Linking Evidence to Action: The three shortened EBP scales, which are valid and reliable, can be used as an alternative to the longer three scales to decrease participant burden when conducting program evaluations, research, or organizational assessments.